The Role of Agricultural Waqf Bank in Strengthening Food Security for Vulnerable Communities: A Mixed-Methods Study - Munir, Misbahul; Kusumah, Echo Perdana; Fauzi, Ahmad Syahrul; Fauzi, Padlun (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: This study examines the role of the Agricultural Waqf Bank in enhancing food security for vulnerable communities in poverty-prone regions, with a secondary focus on the relationship between household income and food vulnerability.Design/methodology: A mixed-methods approach was employed, combining a household survey of 212 vulnerable farming households in South Sumatra, Indonesia, with a qualitative conceptual analysis to develop the Agricultural Waqf Bank model. Logistic regression was applied to estimate the probability of food vulnerability based on household income, while the qualitative analysis explored the model’s design as a sustainable financing mechanism.Findings: Higher household income significantly lowers the likelihood of food vulnerability by enhancing purchasing power and access to food. However, income alone remains insufficient to address structural barriers such as unstable employment, low agricultural productivity, and limited market access. These findings highlight the potential of the Agricultural Waqf Bank model as a sustainable mechanism that integrates productive waqf assets with microfinance, capacity-building, and collective farming strategies to reduce food insecurity among vulnerable communities.Practical Implication: The proposed model provides policymakers and Islamic social finance institutions with a strategic policy design to reduce food insecurity among vulnerable communities by integrating microfinance, technical support, and community empowerment through waqf-based mechanisms.Originality/Value: This study offers a novel and integrated contribution by linking Islamic social finance with food security and community-based poverty reduction, thereby advancing theoretical discourse and informing practical policy design.